Semi-Multiplex PCR Technique for Screening of Abundant Transcripts During Systematic Sequencing of cDNA Libraries. (October 1996) - Pacchioni, B.; Trevisan, S.; Gomirato, S.; Toppo, S.; Valle, G.; Lanfranchi, G.
The systematic sequencing of cDNA libraries is an efficient approach for the identification of new genes, but the presence of abundant mRNAs is often a major problem. This paper describes a very simple method of "semi-multiplex PCR" that allows specific identification of such abundant transcripts before DNA sequencing without using nonrepresentative subtracted libraries. The PCR utilizes a series of forward primers specific for abundant transcripts with a pair of universal primers used for template generation. cDNA clones corresponding to abundant mRNAs are then revealed by double bands in agarose gel.